On the strong almost convergence of double sequences - Başarir, Metin (Kluwer Academic Publishers, 1995)
In this paper, necessary and sufficient conditions that the real doubly infinite matrix A sums every strongly almost convergent double sequence, leaving the limit invariant, have been determined. © 1995 Akadémiai Kiadó.
Keywords: Double sequences; Mathematics subject classification numbers, 1991: Primary 40A05, 40C05, Secondary 40D05; strong almost convergence